MODERNISASI PENDIDIKAN ISLAM DI PONDOK PESANTREN AL-MUHSININ KERINCI. - Muhammad Fadhlan; Firmansyah; Moh. Shollihuddin Fatawi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
The history of modernization and modern terms in boarding schools are very little understood by learners and students in various Istansi. This paper tries to present and describe the modernization of Islamic education in Pondok Pesantren Al-muhsinin both in terms of History in the early and final priode, Learning Curriculum, Learning System, Learning Methods, Modernization Process of education in Indonesia The focus on this paper is to examine the Process of Modernization of Islamic Education in Pondok Pesantren Al-Muhsinin Kerinci. which elements include: History of Modernization of Islamic Education in Pondok Pesantren Al-muhsini, Curriculum of Early and Late-Period Learning, Learning Methods, Evaluation of learning and so on. The methodology used in analyzing the data is The Huberman Mails research model which is divided into three stages, namely: Observation, Interview, and Documentation. The results of this paper are as follows: Modernization of Islamic Education in Pondok Pesantren Al-muhsinin includes changes in the learning curriculum. The learning methods taught are very varied different from before. Evalution is carried out in the form of quarterly and six months. Evlausi includes: Affirmative, Cognitive and Psychomotor.